Analisis Kebijakan Dividen Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Pada Periode Expansi Industri - Pandu Adi Cakranegara (Jurnal Akuntansi, 2021)
Dividend decisions in the company affect investor expectations and in turn affect the value of the company. Therefore, dividend decision is a matter of concern to management. In the 2016 to 2019 period, Indonesia's food and beverage industry experienced growth. This study examines the factors that influence the dividend policies of food and beverage companies in Indonesia in the 2016 to 2019 growth period. These factors are profitability, liquidity and leverage. Furthermore, the moderating variable, namely sales growth, is used to see whether sales growth affects profitability and subsequently affects dividend policy. The method used in this research is multiple linear regression using panel data. The selected sample uses purposive sampling to find companies that consistently provide dividends that come from profits and not from debt or other sources of funds. The findings of this study are that profitability, liquidity and leverage have a significant effect. However, profitability and liquidity do not have a significant positive relationship but have a significant negative relationship. This difference is because when an industry grows, the company invests its funds internally to pursue growth so that the allocation of funds used for dividends is reduced.